آن لائن صارفین کے حقوق: اسلامی اصولوں اور عالمی قوانین کے تناظر میں تقابلی و تجزیاتی جائزہ: Online Consumer Rights: A Comparative and Analytical Study in the Context of Islamic Principles and International Laws - Dr. Taswar Hussain; Dr. Faryal Umbreen (Al-Amīr Research Journal for Islamic Studies, 2025)
This research critically examines online consumer rights in the context of Islamic principles and international laws. The growing trend of e-commerce and digital transactions has highlighted the importance of protecting consumer rights in the virtual marketplace. Islamic jurisprudence provides a comprehensive framework emphasizing justice, transparency, and the prevention of exploitation, principles that remain highly relevant in the modern online economy. On the other hand , international laws and agreements, such as those established by the United Nations and regional frameworks, offer mechanisms to ensure consumer protection in the digital sector. The study highlights areas of convergence and divergence between these two systems, focusing on topics such as fraud prevention, data privacy, consumer awareness, and dispute resolution. By critically analyzing these elements, the research provides insights into how Islamic teachings can complement existing legal frameworks to foster an ethical and inclusive digital marketplace. Finally, the study suggests methods to harmonize these systems to enhance the effectiveness of online consumer rights protection. Keywords: Online Consumer Rights, Islamic Principles, International Laws, E-commerce, Digital Transactions, Virtual Marketplace, Islamic Jurisprudence, Justice, Transparency, Data Privacy